INFORMATION SECURITY OF THE DEFENSE FORCES IN UKRAINE:: CURRENT STATE AND PROSPECTS - O. Zolotar, Olha; M. Zaitsev, Mykola; V. Topolnitskyi, Vitalii; I. Bieliakov, Kostiantyn; M. Koropatnik, Ihor (Revista Gênero e Interdisciplinaridade, 2020)
The relevance of the article is determined by the fact that security is always one of the priority issues of state policy, and given the fact that the defense forces are an integral part of the state’s security, the study of their information security is necessary. The feasibility of this study is confirmed by the fact that in the current conditions of the information society development, information technologies of the Ukrainian defense forces need to adapt to existing challenges and threats in order to ensure adequate protection of information that is of strategic importance to the state and is collected, summarized, stored by the defense forces. The purpose of the article is to identify the problems of information protection of the defense forces in Ukraine, to find areas of their elimination. Formal logical, system structural, comparative legal methods were used to conduct the study. It is noted that by separating the information space and cyberspace, the legislator has complicated the legal regulation of the protection of the state’s information space. It is noted that efforts to prevent threats to the information space in Lithuania and Latvia have been consolidated within the structure of the Ministry of Defense. Accordingly, the authors emphasize the need for the optimization of the system of entities responsible for the protection of the information space, the creation of conditions for public-private cooperation in this area, as in the case of Germany, and the provision of these entities with qualified employees. The results obtained are important for the research, lawmaking and law enforcement activities.